Ilizarov method as limb salvage in treatment of massive femoral defect after unsuccessful tumor arthroplasty - Radunović, Aleksandar; Košutić, Milimir; Vulović, Maja; Milev, Boško; Janjušević, Nataša; Ivošević, Anita; Krulj, Vladimir (Vojnosanitetski pregled, 2017)
Introduction. Surgical management of massive bone defects is very challenging in terms of estimating possibilities of saving the extremity and adequate method that can make it possible. Selection of methods is additionally limited in the presence of infection at site of defect. Case report. The female patient, diagnosed with Ewing sarcoma was treated by segmental bone resection and implantation of Kotz modular tumor endoprosthesis. After 5 years the signs of infection occured and persisted with low grade intensity. After falling, 12 years following implantation, the patient acquired periprosthetic fracture. Then endoprosthesis was removed, all along with surgical debridement of wound and application of the Ilizarov apparatus. The apparatus was applied, osteotomy of callus and the tibia performed with transport of bone segments, untill reconstruction of defect and arthrodesis of the knee was achieved. Conclusion. The Ilizarov apparatus offered us huge possibilities for management of massive bone defects with natural bone which has superior biomechanical characteristics comparing to the implant. The most frequent complication of this method is a prolonged treatment period that demands good patient selection and preparation and wide surgical experience.